2018
DOI: 10.3390/rs10071001
|View full text |Cite
|
Sign up to set email alerts
|

A Conservative Downscaling of Satellite-Detected Chemical Compositions: NO2 Column Densities of OMI, GOME-2, and CMAQ

Abstract: A conservative downscaling technique was applied when comparing nitrogen dioxide (NO 2 ) column densities from space-borne observations and a fine-scale regional model. The conservative downscaling was designed to enhance the spatial resolution of satellite measurements by applying the fine-scale spatial structure from the model, with strict mass conservation at each satellite footprint pixel level. With the downscaling approach, NO 2 column densities from the Ozone Monitoring Instrument (OMI; 13 × 24 km nadir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…We find that AQS measurements from earlier time windows show slightly better agreement with OMI (r 2 =0.64 for 12:00 LST versus r 2 =0.59 for 13:00 LST, see table S1), which may be due to the lag between surface and column diurnal cycles (Fishman et al 2008). Our spatial correlation coefficients agree with prior work reporting spatial correlation of OMI with AQS monitors, including a comparison of 208 moni- Kim et al (2018) also found a correlation coefficient of r 2 =0.67 for GOME-2A.…”
Section: Diurnal Cycle Of Nosupporting
confidence: 83%
See 1 more Smart Citation
“…We find that AQS measurements from earlier time windows show slightly better agreement with OMI (r 2 =0.64 for 12:00 LST versus r 2 =0.59 for 13:00 LST, see table S1), which may be due to the lag between surface and column diurnal cycles (Fishman et al 2008). Our spatial correlation coefficients agree with prior work reporting spatial correlation of OMI with AQS monitors, including a comparison of 208 moni- Kim et al (2018) also found a correlation coefficient of r 2 =0.67 for GOME-2A.…”
Section: Diurnal Cycle Of Nosupporting
confidence: 83%
“…Different approaches have been used to mitigate the smoothing effect for NO 2 when comparing instruments of different resolution. Methods include the regridding of the finer resolution instrument to larger grids (Boersma et al 2008(Boersma et al , 2009), down-sampling finer pixels by averaging them into larger pixels (Hilboll et al 2013), and 'downscaling' satellite data using a model (Kim et al 2018). We explore the potential and limitations in deriving diurnal change from polar-orbiting satellites at smaller scales, using both a re-gridding approach as well as a down-sampling approach.…”
Section: Reconciling Surface and Column No 2 Variabilitymentioning
confidence: 99%
“…To compare satellite models, conducting a fair comparison by matching spatial resolution and vertical sensitivity is crucial [62][63][64]. In this study, we processed satellite data using oversampling based on the conservative spatial regridding method and applied the average kernel to the modeled layers before integrating into the column density.…”
Section: Spatial and Vertical Data Processingmentioning
confidence: 99%
“…We apply the method described by Kim et al (2016Kim et al ( , 2018 to downscale OMI NO 2 retrievals, which are then compared with aircraft and Pandora data. This method applies high resolution model-derived spatial-weighting kernels to individual OMI pixels and calculates sub-pixel variability within the pixel.…”
Section: Downscaled Omi No 2 Datamentioning
confidence: 99%